Pengaruh Orientasi Lingkungan Terhadap Green Competitive Advantage Dengan Inovasi Hijau Sebagai Pemediasi - Satria, Muhammad Abil; Rodiah, Siti; Azmi, Zul (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
This study aims to examine and determine the influence of environmental orientation on green competitive advantage with green innovation as a mediator. This research employs a quantitative approach with respondents consisting of financial managers and general managers working in hotels in Pekanbaru City. Data collection methods utilized a questionnaire instrument with saturated sampling technique, resulting in 88 respondents. Data analysis in this study utilized SEM (struktural equation modeling) with Partial Least Square (PLS) approach, and data management was facilitated using SmartPLS 4.0 application. The test results indicate that environmental orientation has a positive and significant influence on green innovation and green competitive advantage. Similar results were obtained for the variable of green innovation, which also had a positive and significant impact on green competitive advantage. Additionally, the researcher found results indicating that environmental orientation influences green competitive advantage through green innovation.